Universal power supply - Mercado, Krystal Claire Manalo (Nanyang Technological University, 2023)
The voltage levels used by various nations' electrical power grids vary. The standard voltage is 120 volts AC at 60 Hz in North America and some regions of South America, whereas it is 220-240 volts AC at 50 Hz in the majority of the rest of the world. Travelers from other countries and enterprises that need to use electrical equipment in various locations throughout the world may encounter difficulties due to the variations in voltage levels between the various nations. When utilized in a different voltage system, electrical devices made for one voltage level can fail to function or sustain damage. This Final Year Project primarily seeks to use concepts and studies of power electronics as well as different power converter topologies to construct a simulation that can adjust the output voltage according to the geographical location. To perform the adjustment, a control strategy called Model Predictive Control (MPC) is used to illustrate this idea. With the different frequencies used in different countries, this project is also able to demonstrate the output voltage waveform according to these frequencies. The important points that will be covered in this study comprise of the literature review done on this topic as well as the simulations done in software PLECS and MATLAB, and its analysis.